2013
DOI: 10.1016/j.limno.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-specific and multiple pressure response of fish assemblages in European running waters

Abstract: We classified homogenous river types across Europe and searched for fish metrics qualified to show responses to specific pressures (hydromorphological pressures or water quality pressures) vs. multiple pressures in these river types. We analysed fish taxa lists from 3105 sites in 16 ecoregions and 14 countries. Sites were pre-classified for 15 selected pressures to separate unimpacted from impacted sites. Hierarchical cluster analysis was used to split unimpacted sites into four homogenous river types based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Land use scenarios had a minor effect on discharge and hydraulic habitat conditions but markedly affected water quality (nitrate concentrations). However, the predicted nitrate changes were well in the tolerance range of the modelled fish species (Wolter et al, 2003;Schinegger et al, 2013) and thus not considered a potential limiting factor for fish (Wolter et al, 2003).…”
Section: Impacts Of Climate and Land Use Change On Fishesmentioning
confidence: 99%
See 1 more Smart Citation
“…Land use scenarios had a minor effect on discharge and hydraulic habitat conditions but markedly affected water quality (nitrate concentrations). However, the predicted nitrate changes were well in the tolerance range of the modelled fish species (Wolter et al, 2003;Schinegger et al, 2013) and thus not considered a potential limiting factor for fish (Wolter et al, 2003).…”
Section: Impacts Of Climate and Land Use Change On Fishesmentioning
confidence: 99%
“…Moreover, it must be noted that this assessment was solely based on the depth and flow preferences of the species, whilst riverine fish are often markedly limited by the availability of gravel substrates for spawning (Mann, 1996;Wolter et al, 2003;Schinegger et al, 2013), which was not considered in this study since the bottom substrate of the study reach was pure sand and only small gravel patches were found in the Treene River.…”
Section: Impacts Of Climate and Land Use Change On Fishesmentioning
confidence: 99%
“…This simplification was necessary to overcome the multitude of combinations from four river types with 129 metrics. Schinegger & Trautwein (2013) focused on metric responses to specific and multiple pressures (hydro-morphological pressures or pollution pressures) and could identify metrics that responded specifically to pollution pressures and hydromorphological pressures. However, human pressures are widespread and Schinegger et al (2011) showed that rivers in the alpine region are predominately affected by hydromorphological pressures, whereas pollution pressures mostly in combination with hydromorphological pressures prevail in LLR.…”
Section: Discussionmentioning
confidence: 99%
“…6). Schinegger & Trautwein (2013) found that most metrics of any functional trait responded to multiple pressures instead to specific pressures. Further research should investigate whether impact strength (e.g., low, medium, and strong) is better explained by density or biomass metrics.…”
Section: Metricsmentioning
confidence: 99%
“…Although HPP is considered as a climate‐friendly energy source, HPPs are also associated with ecosystem degradation and cause pressures like water abstraction (Arthington et al , ; Huckstorf et al , ), hydropeaking (Saltveit et al , ; Schmutz et al , ), impoundments (Reid, ) and fragmentation (Nilsson et al, ). Together with non‐hydropower‐related impacts, these multiple stressors threaten biodiversity (Schinegger et al , ; Trautwein et al , ; Vörösmarty et al , ) and counteract the aims of the EU Water Framework Directive (WFD; 2000/60/EG; European Commission, ) and the Habitats Directive (HD, 92/43/EEC; European Commission, ). Even under consideration of mitigation measures (e.g.…”
Section: Introductionmentioning
confidence: 99%